The Application of Discrete Fourier Transforms in Reducing the Calibration Effort of Indoor Positioning System - Anvar Narzullaev; Zahriddin Muminov; Zainidin Eshkuvatov; Norazmir Mohd Nordin (Akademi Sains Malaysia, 2024)
Non-Indexed Publication